The effect of state self-control on the intertemporal decisions made by individuals with high and low trait self-control - Guan, Yuan; He, Jiamei (PLOS ONE, 2018)
The present study aimed to explore how state self-control influences the intertemporal decisions made by individuals with high and low trait self-control. State self-control, represented by the degree of depletion, was manipulated by conducting Stroop tasks with different levels of difficulty, and the intertemporal decision task was used as a self-control task. Compared with participants with high trait self-control, the preferences of participants with low trait self-control for immediate rewards were more vulnerable to the difficulty of depletion tasks. Throughout the experimental stages, the heart rate variability (HRV) of participants with high trait self-control was significantly higher than that of participants with low trait self-control, indicating that individuals with high trait self-control may have stronger and more stable self-control abilities.